Sports-Associated Cancer Risk: A Narrative Review of Specific Neoplasms in Athletes - Sikorski, Adam; Kadłubowska, Karolina; Gólcz , Julia; Chojnowska , Natalia; Szaryński , Mikołaj; Rytel, Jan; Jakubowska , Paulina; Bursztyn , Michał; Bursztyn , Tomasz; Jakubowska , Martyna; et al. (Quality in Sport, 2025)
Sport is commonly associated with a healthy lifestyle, improved fitness, and enhanced mental well-being. Many studies confirm that regular physical activity reduces the risk of various cancers, such as colorectal, breast, and endometrial cancer. However, specific behaviors linked to competitive or aesthetic sports, including chronic exposure to ultraviolet (UV) radiation, use of anabolic-androgenic steroids (AAS), selective androgen receptor modulators (SARMs), or muscle-building supplements (MBS), may paradoxically increase the risk of malignancies in certain organs. This review aims to synthesize current knowledge on cancers occurring more frequently or with particular relevance in athletes, with focus on diagnostic challenges and public health implications. Literature highlights several cancer types potentially more prevalent or with distinct characteristics in active individuals. These include skin cancers (especially melanoma and non-melanoma), testicular cancer (germ cell tumors), hepatocellular carcinoma (HCC), and rare sarcomas (soft tissue and bone), particularly among athletes using performance-enhancing substances. Cancer symptoms in athletes are often misinterpreted as sports injuries, which may delay diagnosis and worsen prognosis. Still, epidemiological data confirm the protective effect of moderate exercise on overall cancer incidence and mortality. Despite sport’s general oncological benefits, certain athlete groups are at increased cancer risk due to environmental or pharmacological exposures. Clinicians should maintain diagnostic vigilance in young, active patients with persistent, unexplained symptoms, and pursue prompt imaging and histopathology when needed.